AMPK activation by prolonged stimulation with interleukin‐1β contributes to the promotion of GLUT4 translocation in skeletal muscle cells. (13th September 2016) - Takaguri, Akira; Inoue, Saya; Kubo, Takashi; Satoh, Kumi
Abstract: Impaired insulin signaling in skeletal muscle cells causes insulin resistance associated with the onset of type 2 diabetes. Although interleukin (IL)‐1β has been considered to be implicated in the pathogenesis of type 2 diabetes, the action of prolonged stimulation with IL‐1β on the insulin signaling pathway in skeletal muscle cells remains poorly understood. In the current study, we investigated the effect of IL‐1β stimulation on insulin signal transduction from the insulin receptor (IR), resulting in glucose transporter 4 (GLUT4) translocation in skeletal muscle cells. In L6‐GLUT4myc cells, stimulation with IL‐1β for 24 h promoted GLUT4 translocation to the plasma membrane and increased glucose uptake in a concentration‐dependent manner, whereas short‐term stimulation with IL‐1 for up to 6 h did not affect that. In addition, stimulation with IL‐1β for 24 h further increased insulin‐stimulated GLUT4 translocation. Interestingly, stimulation with IL‐1β for 24 h did not cause any change in the phosphorylation of insulin signal molecules IR, insulin receptor substrate (IRS)‐1, Akt, and p21‐activated kinase (PAK1). Stimulation with IL‐1β for 24 h significantly increased AMP‐activated protein kinase (AMPK) phosphorylation and GLUT4 protein expression. Small interfering RNA (siRNA) targeting AMPK1/2 significantly inhibited IL‐1β‐stimulated GLUT4 translocation. These results suggest that prolonged stimulation with IL‐1β positively regulates GLUT4 translocation in skeletal muscle cells. IL‐1β may have a beneficial effect on maintaining glucose homeostasis in skeletal muscle cells in patients with type 2 diabetes.